Intervention on the impact of exposure to PM2.5 air pollution on airway clearance of asthma sufferers through chest physiotherapy - Sholichin Sholichin; Endang Sawitri; Eva Rachmi; Sri Wahyuningsih; Krispinus Duma; Ratna Kusuma; Ika Fikriah; Daniel Tarigan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Exposure to PM2.5 air pollution is a major risk factor for exacerbations and decreased lung function in asthmatics. The World Health Organization has declared air pollution a global health emergency. Fine PM2.5 particles trigger oxidative stress, chronic inflammation, and impaired airway clearance, which exacerbate airway obstruction. Purpose: Analyzing the effectiveness of chest physiotherapy in improving airway clearance in asthma patients exposed to PM2.5. Method: Using a pretest-posttest design, this study compared Peak Expiratory Flow (PEF) values ​​in the first week as a baseline, with values ​​recorded in the second and third weeks after chest physiotherapy intervention. The Wilcoxon test was used to analyze differences in PEF values ​​over time. Results: Analysis showed a significant increase in PEF values ​​between the first and second weeks (Z = -6.88, p < 0.00) and between the first and third weeks (Z = -7.51, p < 0.00). The majority of participants showed an increase in PEF, with positive ratings of 72 in the second week and 75 in the third week, indicating improved airway clearance after the intervention. Conclusion: Chest physiotherapy effectively improves airway clearance and ventilation function in asthma sufferers exposed to PM2.5, thus having the potential to become an applicable and sustainable non-pharmacological, environmentally based nursing intervention.